(untitled) (The Research of Medical Science Review, 2025)
Objective: This review aims to analyze existing literature on the challenges faced by parents of children with genetic disorders, focusing on their perceptions, coping mechanisms, and access to healthcare. It seeks to identify gaps in current research and provide insights for improving support systems and policy interventions. Method and Material: A structured search was conducted in Google Scholar, CINAHL, and PubMed, adapting search terms to each database’s syntax and indexing. Boolean operators (AND/OR) combined keywords, with MeSH terms for PubMed and database-specific headings for CINAHL. Google Scholar required a flexible approach. The initial search yielded 54,348 articles, refined by filters to 6,320. After reviewing titles, abstracts, and backgrounds, 15 studies were selected. Most were qualitative or mixed-method, aligning with the research topic, excluding editorials and letters Results: Parents face multifaceted challenges, including significant emotional distress, financial strain, and societal stigma. Many parents experience heightened anxiety and depression, compounded by a lack of structured support systems. However, coping strategies such as resilience, religious beliefs, and social support networks help mitigate these challenges. Conclusion: Parents face complex challenges regarding their child care that demand comprehensive healthcare, psychosocial support, and policy reforms. Strengthening healthcare infrastructure, increasing community awareness, and establishing structured support systems can enhance parental well-being. Future research should focus on improving access to specialized care, mental health interventions, and policy-driven solutions to support families affected by genetic disorders.